2022
DOI: 10.1073/pnas.2112336119
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the difference in tree species richness between Africa and South America

Abstract: Significance Our full-scale comparison of Africa and South America’s lowland tropical tree floras shows that both Africa and South America’s moist and dry tree floras are organized similarly: plant families that are rich in tree species on one continent are also rich in tree species on the other continent, and these patterns hold across moist and dry environments. Moreover, we confirm that there is an important difference in tree species richness between the two continents, which is linked to a few f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 90 publications
(122 reference statements)
6
16
0
Order By: Relevance
“…Our results showed that, on average, the Neotropical and Southeast Asian TCs harbour the richest known area-adjusted floras globally and are considerably richer than those from the continental Afrotropics, thus confirming the findings of several previous studies (Richards 1973, Gentry 1992, Kreft and Jetz 2007, Parmentier et al 2007, Couvreur 2015, Silva de Miranda et al 2022. However, the diversity of the richest TCs is rivalled by that of some MCs, namely the Mediterranean Basin and especially the Cape -plant diversity of the latter MC is second only to that of Neotropical Ecuador.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that, on average, the Neotropical and Southeast Asian TCs harbour the richest known area-adjusted floras globally and are considerably richer than those from the continental Afrotropics, thus confirming the findings of several previous studies (Richards 1973, Gentry 1992, Kreft and Jetz 2007, Parmentier et al 2007, Couvreur 2015, Silva de Miranda et al 2022. However, the diversity of the richest TCs is rivalled by that of some MCs, namely the Mediterranean Basin and especially the Cape -plant diversity of the latter MC is second only to that of Neotropical Ecuador.…”
Section: Discussionsupporting
confidence: 91%
“…While most of these patterns can be predicted by simply analyzing continental shapes across latitudes in a mid-domain perspective (Jetz and Rahbek, 2001), biodiversity differences between regions requires a deeper understanding of present and past stability in terms of both climate and geomorphology. For example, in tropical rainforest biodiversity, the Neotropics stand out in terms of species diversity (Barthlott et al, 1996;Hawkins et al, 2007;Hagen et al, 2021), but Southeast Asia reigns in terms of higher-level phylogenetic diversity (Procheş et al, 2015) in both plants and vertebrates, while Africa is comparatively impoverished for both measures (Parmentier et al, 2007;Silva de Miranda et al, 2022). In contrast, for Mediterranean-climate systems, South Africa's Cape is exceptionally diverse, which has been explained by a combination of relative climatic stability and topographic heterogeneity (Cowling et al, 2015).…”
Section: Global Patterns Long-term Processesmentioning
confidence: 99%
“…Just 67 plant genera (Dexter et al, 2015) and 81 families (de Miranda et al, 2022) are shared between savannas on the two continents. Most shared families are thought to have evolved after the split of Gondwana (de Miranda et al, 2022;Dexter et al, 2015), and moist and dry forest biomes are more similar on a given continent than are the floras of either moist or dry biomes across continents (de Miranda et al, 2022). It is therefore probable that savanna floras evolved independently at the continental scale from wet forest vegetation during periods of increased drying during the Miocene (de Miranda et al, 2022;Simon et al, 2009).…”
Section: A Cross-continental Comparison Of Savannasmentioning
confidence: 99%
“…In the cerrado, most plant lineages diversified less than 4 million years ago (Simon et al, 2009), when large mammal herbivores were still present (Malhi et al, 2016;Sandom et al, 2014). Just 67 plant genera (Dexter et al, 2015) and 81 families (de Miranda et al, 2022) are shared between savannas on the two continents. Most shared families are thought to have evolved after the split of Gondwana (de Miranda et al, 2022;Dexter et al, 2015), and moist and dry forest biomes are more similar on a given continent than are the floras of either moist or dry biomes across continents (de Miranda et al, 2022).…”
Section: A Cross-continental Comparison Of Savannasmentioning
confidence: 99%
See 1 more Smart Citation